Understanding Children's Work : An Interagency Data and Research Cooperation Project - Fyfe, Alec; Roselaers, Frans; Tzannatos, Zafiris; Rosati, Furio (Washington, DC: World Bank, 2014)
During the 1990s broad interest resurfaced among the public and policymakers on the subject of child labor, this time concentrating on the plight of children in the developing world. The children summit in New York (1990), the world summit on social development in Copenhagen (1995), and the International Labour Organization (ILO) adoption of convention 182 on elimination of the worst forms of child labour (1999) are clear evidence of the increasing international concern. In several conferences leading up to the 1999 ILO convention (Geneva 1996, Amsterdam 1997, Cartagena 1997, and Oslo 1997), the same commitment to combat child labor was expressed, along with the need for closer cooperation between international organizations, a point emphasized especially in Oslo. With the adoption of the millennium development goals in 2000, the realization quickly grew that international and national efforts to address key developmental objectives will objectives will be hampered unless there are adequate data for measuring monitoring and managing results; sufficient capacity to use the data at the local level supplemented by technical assistance; donor harmonization of policies for setting global (rather than donor) priorities and exploring synergies among all stakeholders; and conditional on the previous three areas timely and relevant policy interventions.